Fracturing in the footwall at the Kiirunavaara mine, Sweden - Nilsson, Mikael; Saiang, David; Nordlund, Erling (Luleå tekniska universitet, Geoteknologi, 2014)
The Kiirunavaara mine is a large scale sub level caving (SLC) mine located near the city of Kiruna in northern Sweden. It is owned and operated by LKAB (Luossavaara-Kiirunavaara AB). The mine produces approximately 28 million tonnes of iron ore annually. Over the last 30 years the mine has experienced a slow but progressive fracturing and movement in the footwall rock mass induced by the SLC operations. The footwall contact which assumes a “slope-like” geometry is partially supported by the caved material from the hangingwall. However, since the late 1980s damage has been observed on the footwall crest as well as within the footwall. Progressive rock mass movement in the footwall is indicated by surface subsidence and visual observations underground. The extent of the damage has traditionally been estimated using empirical relations. Most of the current long term underground infrastructure within the footwall is located at a considerable distance from the ore contact. However, for new developments on deeper levels it is imperative to predict the future extent of the damage volume. Approximating the position of the damage boundary in the footwall at the current state of mining would assist in predicting the extent and characteristics of the damage volume as the mine deepens. LKAB and LTU (Lulea University of Technology) have therefore initiated a joint research project to study the long term stability of the footwall at the Kiirunavaara mine. This paper constitutes part of the work in this research.The paper describes a damage mapping campaign and subsequent analysis of the Kiirunavaara mine footwall to approximate the outer boundary of the damage. The footwall was systematically mapped on 6 levels between 320 and 800 m. The mapping results were then used to interpolate damage lines on the respective levels. The damage lines were used to construct a continuous damage surface between the studied levels. Existing records of damage mapping, monitoring and predictions were reviewed and compared to the results from ...